Stay awake : stories - Chaon, Dan (Ballantine Books, 2012)
"Before the critically acclaimed novels Await Your Reply and You Remind Me of Me, Dan Chaon made a name for himself as a renowned writer of dazzling short stories. Now, in Stay Awake, Chaon returns to that form for the first time since his masterly Among the Missing, a finalist for the National Book Award. In these haunting, suspenseful stories, lost, fragile, searching characters wander between ordinary life and a psychological shadowland. They have experienced intense love or loss, grief or loneliness, displacement or disconnection--and find themselves in unexpected, dire, and sometimes unfathomable situations. A father's life is upended by his son's night terrors--and disturbing memories of the first wife and child he abandoned; a foster child receives a call from the past and begins to remember his birth mother, whose actions were unthinkable; a divorced woman experiences her own dark version of "empty-nest syndrome"; a young widower is unnerved by the sudden, inexplicable appearances of messages and notes--on dollar bills, inside a magazine, stapled to the side of a tree; and a college dropout begins to suspect that there's something off, something sinister, in his late parents' house. Dan Chaon's stories feature scattered families, unfulfilled dreamers, anxious souls. They exist in a twilight realm--in a place by the window late at night when the streets are empty and the world appears to be quiet. But you are up, unable to sleep. So you stay awake"--